1999
DOI: 10.1046/j.1365-2958.1999.01669.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous tandem amplification and deletion of the Shiga toxin operon in Shigella dysenteriae 1

Abstract: SummaryOnly one species of Shigella, Shigella dysenteriae 1, has been demonstrated to produce Shiga toxin (Stx). Stx is closely related to the toxins produced by Shiga toxin-producing Escherichia coli (STEC). In STEC, these toxins are often encoded on lambdoid bacteriophages and are major virulence factors for these organisms. Although the bacteriophageencoded stx genes of STEC are highly mobile, the stx genes in S. dysenteriae 1 have been believed to be chromosomally encoded and not transmissible. We have loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 63 publications
(96 reference statements)
1
73
1
Order By: Relevance
“…Only the stx # phage 933W appeared to be a fully functional phage, while the other λ-like sequences showed a mosaic structure, indicating extensive exchange of genes. Another STEC O157 : H7 isolate that is currently being sequenced also has many phage-like sequences in its genome (Yokoyama et al, 2000), and a similar phenomenon has also been observed in Shigella dysenteriae (McDonough & Butterton, 1999). The general position of the stx genes in Stx-encoding phages appears to be conserved, as they are located between the genes encoding the transcription antiterminator Q protein and the holin S gene of the lysis cassette (Plunkett et al, 1999 ;Unkmeir & Schmidt, 2000).…”
Section: Introductionmentioning
confidence: 81%
“…Only the stx # phage 933W appeared to be a fully functional phage, while the other λ-like sequences showed a mosaic structure, indicating extensive exchange of genes. Another STEC O157 : H7 isolate that is currently being sequenced also has many phage-like sequences in its genome (Yokoyama et al, 2000), and a similar phenomenon has also been observed in Shigella dysenteriae (McDonough & Butterton, 1999). The general position of the stx genes in Stx-encoding phages appears to be conserved, as they are located between the genes encoding the transcription antiterminator Q protein and the holin S gene of the lysis cassette (Plunkett et al, 1999 ;Unkmeir & Schmidt, 2000).…”
Section: Introductionmentioning
confidence: 81%
“…The stx gene of S. dysenteriae type 1 is also encoded in a phage remnant. Here, the stx operon is flanked by a number of insertion elements and only a small number of phage genes remained (McDonough et al, 1999) so that the prophage character of this element is archetypal. On the basis of sequence analysis, CP-1639 is considered to be a victim of a single or multiple recombination events, that left behind a handicapped mosaic phage genome.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, integration of Stx phage DNA into E. coli chromosomes may play a key role in the emergence of new STEC pathotypes (Schmidt, 2001). The stx genes may also be present in defective prophage genomes as is the case for stx of Shigella dysenteriae and for stx 1 in E. coli O157 : H7 strain EDL933 (McDonough et al, 1999;Perna et al, 2001). Although the number of published phage genomes and chromosomal integration sites is growing, only a few such sites are known for Stx phages.…”
Section: Introductionmentioning
confidence: 99%
“…The lambda phage receptor was put into DBS100, creating DBS100/pTroy9, and induced by growing overnight at 37°C in lambda broth with 0.2% maltose and 10 mM MgSO4. This strain was then lysogenized with the antibioticmarked bacteriophages as described previously (118), resulting in DBS770 [C. rodentium (λstx2dact)] or DBS771 [C. rodentium (λstx2dact::kan R )].…”
Section: Construction Of C Rodentium (λStx2dact) and C Rodentium (λmentioning
confidence: 99%